Impact of sequential (first- to third-generation) EGFR-TKI treatment on corrected QT interval in NSCLC patients - Gan, Tian; Chen, Jindong; Wang, Hao; Shang, Conghui; Xi, Siqi; Fan, Zixu; He, Ben; Zhang, Min; Zhao, Liang (Frontiers in Oncology, 2024)
Objective To evaluate the impact of sequential (first-to third-generation) epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) treatment on top corrected QT-interval (top-QTc) in non-small cell lung cancer (NSCLC) patients.We retrospectively reviewed the medical records of NSCLC patients undergoing sequential EGFR-TKI treatment in Shanghai Chest Hospital between October 2016 and August 2021. The heart rate (HR), top-QT-interval, and top-QTc of their ECGs were extracted from institutional database and analyzed. Logistic regression was performed to identify predictors for top-QTc prolongation. Results Overall, 228 patients were enrolled. Compared with baseline (median, 368ms, same below), both first-generation (376ms vs. 368ms, p<0.001) and sequential thirdgeneration EGFR-TKIs (376ms vs. 368ms, p=0.002) prolonged top-QT-interval to a similar extent (p=0.635). Top-QTc (438ms vs. 423ms, p<0.001) and HR (81bpm vs.79bpm, p=0.008) increased after first-generation EGFR-TKI treatment. And further top-QTc prolongation (453ms vs. 438ms, p<0.001) and HR increase (88bpm vs. 81bpm, p<0.001) occurred after treatment advanced. Notably, as HR elevated during treatment, top-QT-interval paradoxically increased rather than decreased, and top-QTc increased rather than slightly fluctuated. Moreover, such phenomena was more significant after treatment advanced. After adjusting confounding factors, pericardial effusion and lower serum potassium level were independent predictors for additional QTc prolongation during sequential third-generation EGFR-TKI treatment. Conclusion First-generation EGFR-TKI could prolong top-QTc and sequential thirdgeneration EGFR-TKI induced further prolongation. Top-QT-interval paradoxically increased and top-QTc significantly increased as HR elevated, which was more significant after sequential EGFR-TKI treatment. Pericardial effusion and lower serum potassium level were independent predictors for additional QTc prolongation after sequential EGFR-TKI treatment.